Pembangunan Berkelanjutan: Analisis terhadap UULLAJ - Zairin Harahap (Fakultas Hukum Universitas Islam Indonesia, 2000)
If sustainable development does not constitute a green camouflage; the slogan must be implemented in every government policy. One of these is in the field of regulation. This paper tries to study the traffic regulations (Undang-Undang Lalu Lintas dan Angkutan Jalan) whether it has been in line with the essence of the sustainable development concept or it is Just the green camouflage.